Defence is the Best Offence: Horizontal Disintegration and Institutional Completion in the German Coordinated Market Economy. (June 2019) - Hertwig, Markus; Kirsch, Johannes; Wirth, Carsten
The article considers how (new) forms of horizontal disintegration, like onsite subcontracting, challenge and change the industrial relations institutions of the German coordinated market economy (CME). Focusing on firm-level co-determination practices, it analyses how works councils respond to strategies of onsite subcontracting and what effects their responses have for the employment system. Based on evidence from 12 case studies, it is argued that although onsite subcontracting might prompt institutional erosion, this does not pass uncontested. Rather, practices of network-oriented employee representation on the part of works councils might bring about an 'institutional completion', in this case, the institutionalisation of the network as an additional point of reference for employee representation. This may stabilise and even extend the scope of existing CME institutions through a process of 'institutional upgrading'. In some areas of the economy, however, management and works council practices are more likely to exacerbate dualisation and social inequality.